Technological Pedagogical Content Knowledge (TPACK): Survey Persepsi pada Mahasiswa Calon Guru IPA - Ayu Lestari; Dea Santika Rahayu (UNIB Press, 2023)
Technological Pedagogical Content Knowledge (TPACK) refers to a combination of three crucial elements: pedagogical knowledge, content knowledge, and the integration of technology used by teachers in the learning. TPACK knowledge is needed to improve the quality of pre-service science teachers. This study aims to describe the perceptions of pre-service science teachers regarding TPACK knowledge. This research was survey research using a quantitative descriptive method involving 60 students at Universitas Tidar. Data were collected using a self-assessment questionnaire containing 31 items that include 7 (seven) TPACK indicators, namely Content Knowledge (CK), Pedagogical Knowledge (PK), Technological Knowledge (TK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), and Technological Pedagogical Content Knowledge (TPACK). Data were analyzed within 3 (three) stages, i.e. data reduction, data display, and drawing conclusions. Furthermore, the data were converted into qualitative assessment criteria to describe the perceptions of pre-service science teachers. The results showed that the TPACK knowledge of pre-service science teachers was categorized as good. The findings are expected to be a reference in improving the education program.